Comparative analysis of quantitative dermatoglyphic markers in schizophrenia patients and controls attending a superspeciality hospital in West Bengal - Pal, Amit Kumar; Ray, Sagarika; Bhattacharya, Jishnu (International Journal of Research in Medical Sciences, 2021)
Background: Schizophrenia is a psychiatric disorder encompassing multiple etiological variables. Association of dermatoglyphic traits with schizophrenia has been observed and reported. This study was undertaken to evaluate epidermal ridge patterns in patients of schizophrenia as compared to healthy controls attending a superspeciality hospital in West Bengal. Establishing dermatoglyphic parameters as biomarkers for early diagnosis will ensure prompt intervention and a greater scope of recovery in schizophrenia and thus promote a better quality of life for the individual as well as lower the burden of disease for the society. Methods: Quantitative dermatoglyphic parameters namely, total finger ridge count (TFRC), total A-B ridge count (TABRC) and ATD angle of 50 schizophrenia patients were compared to 50 age and gender matched healthy controls. Results: TFRC and TABRC were found to be decreased in schizophrenia, while ATD angle was increased in schizophrenia as compared to the control group. Conclusions: This study found a significant association between dermatoglyphic pattern anomalies and the development of schizophrenia. This may offer a scope of primordial prevention of schizophrenia in future, utilising dermatoglyphics as an investigative tool.